IMPROVING STUDENT’S READING ABILITY BY STORY STAR STRATEGY ON NARRATIVE TEXT - Lestari, Wulan Dwi; Suhartono, Luwandi; Husein, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was aimed to improve students’ reading ability in finding out the understanding details on narrative text of SMP N 1 Kecamatan Sandai through Story Star strategy. This study was conducted through a classroom action research which it treated the students in three cycles. The subject of the research was class VIII which consists of 39 students. The data was collected using observation checklist and field notes. It also used mean score. The result of the study showed that Story Star strategy could improve the students’ reading ability after three cycles. The improvement to students’ reading ability was better in the third cycle than the first and second cycle which was shown by the mean score of student’s achievement. On the first cycle the students’ mean score was 48.28, and then improved to 62.05 and up to 76.52. Keywords : Story Star Strategy, Narrative Text,  Reading ability Abstrak: Penelitian ini ditujukan untuk meningkatkan kemampuan membaca siswa dalam menemukan informasi yang terperinci dalam naratif teks di SMP N 1 Kecamatan Sandai melalui Story Star Strategy. Pembelajaran ini dilaksanakan melalui penelitian tindakan kelas dimana siswa diuji dalam tiga siklus. Subjek dalam penelitian ini adalah kelas VIII yang berjumlah 39 siswa. Pengumpulan data menggunakan lembar observasi dan catatan lapangan. Analisa data juga dilakukan dengan cara mencari nilai rata-rata. Hasil dari penelitian menunjukkan bahwa Story Star dapat meningkatkan kemampuan membaca siswa setelah tiga siklus. Peningkatan kemampuan membaca siswa lebih baik pada siklus ketiga daripada siklus pertama dan kedu sebagaimana yang ditunjukkan oleh hasil rata-rata dari hasil yang di capai siswa. Pada siklus pertama, rata-rata siswa adalah 48.28, pada siklus kedua rata-rata adalah 62.05, dan meningkat di siklus ketiga dengan rata-rata adalah 76.52. Kata kunci : Strategi story star, Teks Naratif, kemampuan dalam membaca